COMPARATIVE EFFICACY OF CHRONIC HEART FAILURE TREATMENT WITH PERINDOPRIL OR CARVEDILOL IN PATIENTS WITH ALCOHOLIC OR IDIOPATHIC DILATED CARDIOMYOPATHY - I. V. Zhirov; G. K. Sarbalinova; S. N. Tereschenko (Рациональная фармакотерапия в кардиологии)
Aim. To study the clinical and hemodynamic efficacy of monotherapy with ACE inhibitor perindopril or beta-blocker carvedilol in patients with chronic heart failure (CHF) due to dilated cardiomyopathy (DCMP) of various etiology.Material and methods. Patients (n=69) with DCMP of different etiology were included into the open randomized study. Idiopathic DCMP (IDCMP) was diagnosed in 26 patients and alcoholic cardiomyopathy (ACMP) - in 43 patients. Patients of IDCMP and ACMP groups were randomized for treatment with perindopril (groups 1 and 3, respectively) or carvedilol (groups 2 and 4, respectively). Follow-up was 6 months. End-diastolic and end-systolic left ventricular volume, stroke volume index, ejection fraction (EF) and exercise capacity were determined at baseline and in 2 and 6 months of treatment. Safety of the treatments was also assessed.Results. Group 1: the average CHF class (NYHA) decreased by 20.7% (p<0.01), EF increased by 18.2% (p<0.05). Group 2: the average CHF class decreased by 29.6% (p<0.01), EF increased by 18.2% (p<0.05). Group 3: the average CHF class decreased by 14.3% (p<0.01), EF increased by 19.6% (p<0.05). Group 4: the average CHF class decreased by 41.4% (p<0.001), EF increased by 32.8% (p<0.001).Conclusion. Monotherapy with carvedilol in patients with ACMP was more effective than this with perindopril. Long-term monotherapy with perindopril or carvedilol in patients with DCMP was well tolerated and safety.